Correlation between Students’ Critical Thinking Ability and Self-Confidence on Junior High School - Malik, Farid Fadhil; Nurdin, Irfan Taufik; Hidayat, Wahyu ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
One way to improve students' affective and cognitive aspects is through a mathematics learning approach method at school. Achievement of learning objectives (CPL) is demonstrated by the extent to which students have achieved learning objective competencies through a series of criteria or indicators that can be seen from student achievement or learning outcomes. The method in this research uses a non-experimental correlational quantitative research method carried out on class VII students at one of the MTS in Soreang, Kab. Bandung. The aim of this research is to get an idea of how self-confidence influences critical thinking skills or the relationship between critical thinking skills and self-confidence. The results of this research show that the correlation between students' critical thinking skills and self-confidence has a "strong" influence on each other. The conclusion of this research is that Ho is rejected so that Hα is accepted: There is an influence between self-confidence and critical thinking on student achievement or learning outcomes, this means that students' self-confidence and critical thinking greatly influence learning outcomes with the regression model obtained Y = 32.788 + 0.399X1 + 0.391X2 Positive correlation occurs when the two variables are related to the same status (the linear regression coefficient has a positive sign). If one variable increases, the other variable also increases, and vice versa if it decreases.